STAGES OF NATIONAL INNOVATION SYSTEM DEVELOPMENT IN RUSSIAN FEDERATION BY CONSIDERING THE SUPPLY CHAIN STRATEGIES - Bodrova, Elena V.; Gorina, Tatiana V.; Kalinov, Viacheslav V. (International Journal of Supply Chain Management, 2019)
Abstract- They conducted the study of national innovation system development stages in Russian Federation on the basis of previously published and archival documents based on the supply chain management. They determined achievements and miscalculations in the development and implementation of state innovation policy at various stages of its implementation. Analysis of scientific literature, conclusions and recommendations of experts, statistical data, archival and published documents made it possible to expand the list of factors blocking innovation processes. The most important conditions for braking overcoming were the following ones: the need to transform the financial and economic policy towards the reconstruction and activation of innovative processes in the country industrial complex; the awareness of modernization aspirations development significance in society by the authorities, the consolidation of entrepreneurship, scientific community and state efforts; the analysis of practical experience, the rejection of erroneous decisions; the consistency in the implementation of the intended.